Paramaterized the shariah rulings for partnership financial transactions - Che Arshad, Noraziah; Ismail, Abdul Ghafar; Ismail, Mohd Adib; Shahimi, Shahida; Ahmad, Shofian; Sulaiman, Ahmad Azam (Universiti Utara Malaysia, 2011)
Bank Negara Malaysia (BNM), the central bank, has already published the draft of its latest Shariah parameter on Mudharabah and Musharakah contract.The general aim of which are to provide a standard guidance on applying respective Shariah contracts in Islamic finance and also to promote the harmonization of Islamic finance market practices in Malaysia.The establishment of shariah parameters is aimed at achieving the following objectives: (i) to clarify concepts, principles and conditions of shariah contracts; (ii) to provide focus on features of shariah contracts that form the basis of Islamic financial product; and (iii) to provide basis for decisions on matters relating to conditions, mechanism and implementation of shariah contracts.The shariah parameter for each financial products could be useful for: (i) facilitating Islamic finance professionals and practitioners to design and develop Islamic financial products; and (ii) formulating the policies and guidelines on contracts adopted by Islamic financial service industry.These parameters will be used to smoothly functioning of Islamic financial institutions in Malaysia.The guidelines aim to promote operational efficiency and best practices that would safeguard the interests of stakeholders and in particular participants. In this research we provide the discussion: a) how i) the features identified in this parameter will serve to assist the Islamic financial services industry to identify, understand, apply and distinguish the contract from other contracts prevalent in the industry; ii) the features identified and described in this parameter are extracted from the text of fatwas opined.b) also focusing critically analyzes on practical constraint faced by Islamic banking in the implementation of Mudharabah financing facilities focus on under three categories: Demand Deposit, Mutual Investment Deposits and Special Investment Deposits.What do we expect from this research may identify if a special rules apply to a types of contract musharakah especially in musharakah al-milk and musharakah al-aqd however contract mudharabah particularly in restricted and unrestricted because their implication on conflict of interest.